Karakoram fault zone rocks cool in two phases - Dunlap, W; Weinberg, R; Searle, M (1998)
The Karakoram fault zone of Ladakh, India, is a major strike-slip boundary along which the tectonic evolution of Tibet has been accommodated. In this paper 40Ar/39Ar isotopic age data are integrated with structural and metamorphic data to infer an exhumation history for granites and low- to intermediate-grade metamorphic rocks exposed adjacent to two strands of the fault zone. Near Tangtse, leucogranites which crystallized c. 17 Ma ago are cut by the Karakoram fault zone, indicating that fault movement was initiated subsequent to 17 Ma. The 40Ar/39Ar data give temperature-time histories which indicate that the <17 Ma metamorphic rocks within the fault zone were exhumed differentially relative to the adjacent (and already cooled to <150°C) Ladakh Batholith, while cooling progressively through amphibolite to below greenschist facies temperatures. Two phases of rapid cooling of Karakoram fault zone rocks are evident, one at c. 17 Ma to c. 13 Ma, and another, following an intervening period of relatively slow cooling, starting at c. 8 Ma and continuing until at least 7 Ma. Uplift since c. 17 Ma via dextral oblique thrusting has resulted in exhumation from amphibolite facies metamorphic conditions, possibly with a larger thrust component from 17 to 13 Ma, followed by a change to dominant strike-slip motion at about 13 Ma. Rapid cooling starting at c. 8 Ma at greenschist facies temperatures is probably the result of renewed oblique thrusting. It is notable that the two episodes of rapid cooling recorded in Karakoram fault zone rocks coincide with episodes of exhumation in the Pakistani Karakoram and also in southern Tibet.